Risk factors associated with breast cancer among women attending a tertiary care hospital in Bangalore: a case control study - D. C., Vidya; C. N., Shalini; B. S., Nandakumar; N. S., Murthy; Nagnoor, Ibrahim (International Journal Of Community Medicine And Public Health, 2018)
Background: Breast cancer is one of the commonest cancers in both developing and developed countries. Owing to regional variations in distribution of risk factors, there is geographical variation in incidence of breast cancer. This study was attempted to assess the modifiable and non-modifiable risk factors associated with breast cancer among women attending a tertiary care hospital. Methods: A hospital based case-control study was carried out in KMIO, Bangalore, India from May 2013 to February 2014. Newly diagnosed primary cases of female breast cancer of any age and one control per case matched by 5 years age class interval were interviewed, using a questionnaire until required sample was met. Statistical analysis was performed using SPSS software version 18.0. Results: The study population consisted of 135 cases of breast cancer and 135 controls. The mean age was 50 years (SD±10.41) and 94 (34.8%) of them belonged to 45-54 years age group. After forward logistic regression, the risk factors significant at P<0.05 were age at first pregnancy >20 years OR 4.49 (95% CI 1.21-16.62), total duration of lactation <48 months OR 7.96 (95% CI 2.20-21.68), consumption of non-vegetarian diet OR 6.96 (95% CI 1.45-33.25), BMI ≥23 OR 4.91 (95% CI 1.25-19.23) and household physical activity ≤120 minutes/day OR 8.52 (95% CI 1.98-36.64), watching television during weekends >180 minutes/day OR 4.64(95%CI 2.71-7.78). Conclusions: The modifiable risk factors of breast cancer include age at first pregnancy, total duration of lactation, non-vegetarian diet, increased BMI and lower household physical activity and non-modifiable risk factor being age at menopause.